2017
DOI: 10.1016/j.jtumed.2017.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Delayed diagnosis in the maxillofacial region: Two case reports

Abstract: While conventional CT scan has historically been used for maxillofacial bone imaging. The introduction of cone beam CT (CBCT) in the new millennium has revolutionized the use of CT for dental and maxillofacial diagnoses. This paper presents two clinical examples of delayed diagnoses associated with maxillofacial imaging, describes the reasons for the delays and offers potential preventive measures. The first case involves a delay in the diagnosis of non-Hodgkin's lymphoma in a 49-year-old female who was being … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Jaw lesion specially in children should be established as early as possible to prevent adverse treatment outcomes and to improve prognosis, 26 there should be multidisciplinary approach in achieving diagnosis of oral lesions specially jaw lesions and practitioners should seek expert advice from other specialist in histopathology and radiology to implement the necessary diagnostic methods to achieve diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jaw lesion specially in children should be established as early as possible to prevent adverse treatment outcomes and to improve prognosis, 26 there should be multidisciplinary approach in achieving diagnosis of oral lesions specially jaw lesions and practitioners should seek expert advice from other specialist in histopathology and radiology to implement the necessary diagnostic methods to achieve diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Heggie et al 23 and Baltensperger et al 24 observed a high incidence and uniformity of features of the disease among children and adolescents, respectively, proposing that the pediatric "variation" should be regarded as a separate clinical entity and suggesting the term "juvenile chronic osteomyelitis" for its description. 25 Jaw lesion specially in children should be established as early as possible to prevent adverse treatment outcomes and to improve prognosis, 26 there should be multidisciplinary approach in achieving diagnosis of oral lesions specially jaw lesions and practitioners should seek expert advice from other specialist in histopathology and radiology to implement the necessary diagnostic methods to achieve diagnosis.…”
Section: Differential Diagnosesmentioning
confidence: 99%
“…2 3 4 For this reason, computers play a larger role in oral radiology than they do in other fields of dentistry. 5…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] For this reason, computers play a larger role in oral radiology than they do in other fields of dentistry. 5 With the ongoing advances in computer-assisted learning (CAL), the question arises as to how best to use this technology to teach oral radiology students. Educational researchers must assess both the efficiency and effectiveness of CAL, establish whether it performs as effectively as traditional teaching does, and identify when and how to use it.…”
Section: Introductionmentioning
confidence: 99%